Characterization and Toxicity of Temulawak Curcuminoid Nanoparticles - Riki Riki; Popi Asri Kurniatin; Laksmi Ambarsari; waras Nurcholis; Latifah K Darusman (IPB University, 2016)
Temulawak exctract contains curcuminoids which have anticancer potential. However, clinical application of curcuminoid has been limited due to its low bioavailability. One of the efforts that can be developed to solve this problem is incorporated curcuminoids into Solid Lipid Nanoparticles (SLN) carriers system. The objective of this study was to characterize dan evaluate anticancer potential of temulawak ethanolic fraction nanoparticles. HPLC method was used to determined curcuminoids content of temulawak ethanolic fraction. Characterization indicators like polydispersity index, particle size, morpholgy, and entrapment efficiency. HPLC chromatogram has shown of curcumin, demethoxycurcumin, and bisdemethoxycurcumin were found in temulawak ethanolic fraction. The particle size of nanoparticles obtained in this study was 648.4 ± 95 nm with polydispersity index value of 0.216. A uniform size distribution of nanoparticles as observed by Transmission Electron Microscopy (TEM). The entrapment efficiency of curcuminoid in nanoparticles was about 29.8%. Based on results of BSLT obtained temulawak extract Lethal Concentration (LC50) value of 213.24 ppm and 828.78 ppm of nanoparticles.